Phylogenetic relationships of Polyporus and morphologically allied genera - Kozue Sotome (2018)
Polyporus accommodates morphologically heterogeneous species and is divided into six infrage-neric groups based on macromorphological characters. On the other hand allied genera have macro- and microscopic characters similar to those of Polyporus. The phylogenetic relationships of Polyporus and allied genera were established from sequences of RNA polymerase II second largest subunit (RPB2), nuclear ribosomal large subunit (nucLSU) and mitochondrial ATPase subunit 6 (ATP6). The molecular phylogenetic trees confirmed that Polyporus is a polyphyletic genus and recognized six major clades (1-6) containing species of Polyporus and several allied genera. Among the clades one contained three infrageneric groups of Polyporus and two allied genera, Datronia and Pseudofavolus while one other contained group Polyporellus and Lentinus. Five of the six major clades contained species belonging to a single infrageneric group, Favolus, Melanopus, Polyporellus or Polyporus. This suggests that morphological characters used to define these groups have phylogenetic significance and reveals the need for a taxonomic revision of Polyporus and its allied genera. © 2008 by The Mycological Society of America.